Analisis hadith Al-Ṯurāyya dan kaitannya dengan COVID-19 - Ramle, Muhamad Rozaimi; Mohamad, Mohd Yusof (Brill, 2020)
COVID-19 has been declared as a global pandemic by World Health Organisation (WHO). Certain Muslims associated the emergence of Al-Ṯurāyya with the fading of Coronavirus Disease 2019 (COVID-19). This article aimed to discuss the text and context of the Hadith Al-Ṯurāyya (الثُريَّـــــــــــا) and its link to the termination of COVID-19. Classical and contemporary scholars’ opinions were analysed in this study. The methodology used involved inductive and deductive supplemented with critical analysis determining the most appropriate opinion on this matter. Further empirical study of the visibility of Al-Ṯurāyya in the Islamic history were analysed using Stellarium Astronomy Software 0.20.0. The findings of the study revealed that the hadith refers to the disappearance of disease pertaining to fruits and crops and not to related to the end of any pandemic. Additionally, the rise of Al-Ṯurāyya showed no connection with pandemic termination in the Islamic history. In conclusion, the claim that COVID-19 will disappear with the emergence of Al-Ṯurāyya can be rejected.